Primary Healthcare Strengthening through Distance Education for Health Professionals - Karunathilake, I.M.; Bandara, J.; Attygalle, D.; Gunawardena, C.N.; Egodage, T.; Chandrasena, U. (South-East Asian Journal of Medical Education, 2020)
Introduction: Primary Health Care is proven to be a highly effective and efficient way to address poor health and well-being. Despite its achievements Sri Lanka’s PHC System, specialized for preventive and curative actions, is increasingly under pressure due to chronic and non-communicable diseases. Developing the broad range of skills necessary for medical practice in the existing PHC settings should be achieved through continuous professional development. A distant learning programme through eLearning is a model solution to expand the existing boundaries for CPD. Methods: Sri Lanka Medical Association, Ministry of Health, Primary Healthcare System Strengthening Project and World Bank have collaboratively worked as key stakeholders to develop and implement a course for capacity building among the medical professionals. The first phase of the course was developed with 6 priority modules consisting of Ministry of Health approved content conjoined with digital material. Participants were provided with additional resources. The course was evaluated by assessing user involvement and users’ perception towards the course. The course reflected a positive involvement for majority of modules and a generally positive feedback despite the response rate being considerably low. Discussion: Vulnerabilities in the system could be identified including shortcomings of the system, instructors and learning material, and administration issues. Including diverse course materials, provision of incentives for participation, training resource persons and other recommendations may allow better distance learning experience with desired outcomes. Conclusion: Distance learning through an eLearning platform is an ideal way to address CPD in PHC through timely modules, appropriate learning material, user friendly interface, efficient evaluation methods, and an effective system improving procedure. This course has enabled medical professional to develop their insights in PHC, however the shortcomings should not be neglected.
Keywords: Primary Health Care; Continuous Professional Development